2020
DOI: 10.1101/2020.11.03.20211847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selecting the most effective DBS contact in essential tremor patients based on individual tractography

Abstract: Postoperative choice of the most effective DBS contact in patients with essential tremor (ET) so far relies on lengthy clinical testing. It was shown that postoperative effectiveness of DBS contacts depends on the distance to the dentatorubrothalamic tract (DRTT). Here, we investigated, whether the most effective DBS contact could be determined from the stimulation overlap with the individual DRTT. Seven ET patients with bilateral thalamic deep brain stimulation were included retrospectively. Tremor control wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Crucially, however, although retrospective screening of patient records in the Berlin and Florida cohorts revealed no intolerable side effects at 12-month follow-up, the lack of recorded minor stimulationinduced adverse events prevented their direct investigation in the present study (similar to several recent studies suggesting efficient tremor suppression along the entirety of DRT). 2,38 Further prospective validation is required to characterize the side effect profile of the hypointensity marker.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, however, although retrospective screening of patient records in the Berlin and Florida cohorts revealed no intolerable side effects at 12-month follow-up, the lack of recorded minor stimulationinduced adverse events prevented their direct investigation in the present study (similar to several recent studies suggesting efficient tremor suppression along the entirety of DRT). 2,38 Further prospective validation is required to characterize the side effect profile of the hypointensity marker.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 18, 2023. ; https://doi.org/10.1101/2023.01.17.23284553 doi: medRxiv preprint Assessment of white matter tracts offer an additional approach to assess brain structure in relation to DBS outcomes. The dentatorubrothalamic tract (DRTT) is a tract that has gained increasing popularity for importance of DBS outcomes in movement disorders including Parkinson's disease and essential tremor, (25)(26)(27)(28) but has yet to be explored in cervical dystonia. Originating at the dentate nucleus of the cerebellum, classically defined decussating and more recently disclosed nondecussating tracts, convey cerebellar output to the thalamus, with onward projections to sensorimotor cortex.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Even with Vim-DBS, the optimal site is not definitive, and lead placement with MER and test stimulation is common. Recently, segmentation of the thalamic nuclei 53) and detection of optimal site using imaging methods such as drawing the dentato- rubro-thalamic tract 54 , 55) and connectivity analysis 56) have become possible thanks to advances in imaging technology. On the other hand, Gravbrot, et al reported that about 12 patients received asleep D-lead implantation to Vim for ET.…”
Section: Introductionmentioning
confidence: 99%